Morphometric analysis of maxillary arch dimensions using Cone Beam Computer Tomography (CBCT) - R.M. Jayasinghe; I.P. Thilakumara; P.V.K.S. Hettiarachchi; M.C.N. Fonseka; C.D. Nanayakkara; R.D. Jayasinghe (Elsevier, 2022)
Knowledge of morphology of the maxillary arch is important in many spacialities of dentistry. This retrospective cross-sectional study was performed using 109 randomly selected maxillary CBCT images of patients in the age range of 18-60 from the archives in Faculty of Dental Sciences, University of Peradeniya, Sri Lanka. EzDent software was used for measurements. Measurements related to the width were acquired from coronal sections while the measurements related to antero-posterior dimensions were performed on axial sections. A majority had an oval shaped maxillary arch (64.8%) followed by V shaped one.(29.2%). The mean height of the alveolar ridge at the upper canine position was 8.9 mm and the mean height of the alveolar ridge at the first molar level was 20.1 mm. Mann Whitney U test was used to compare measurements of variables between males and females. Difference in the height of alveolar ridge at the junction of soft and hard palate, width of the alveolar ridge at the canine, first molar and second molar and also the antero-posterior distance of the arch at the inter canine distance and junction between the hard and soft palate were statistically significant. Kruskal Wallis test was used to compare the differences between age groups. Chisquare values didnot indicate significant differences of measurements according to the age group of the participants. In conclusion, there is a significant difference in all maxillary arch parameters between the different genders. No significant differences in arch parameters were observed among the different age groups.